A comprehensive prognostic and immune infiltration analysis of EXOC3L1 in pan-cancer - Zhang, Zhan-Fei (Frontiers in Genetics, 2022)
Exocyst complex component 3 like 1 (EXOC3L1) is widely present in various human tissues, which mainly regulates insulin secretion. However, its roles in tumors remain unclear. In the present study, we aimed to investigate the roles of EXOC3L1 in pan-cancer, and the data was downloaded from of the University of California Santa Cruz (UCSC) Xena and the Cancer Genome Atlas (TCGA). The expression status of EXOC3L1 was studied in the TCGA_GTEx samples, TCGA samples and paired samples in TCGA, respectively. Subsequently, Kaplan-Meier analysis was applied to 33 kinds of tumors in TCGA, among the cancers that EXOC3L1 can affect prognosis, clinical correlation analysis and univariate Cox regression analysis were performed. Furthermore, representative cancers kidney renal clear cell carcinoma (KIRC) and lung squamous cell carcinoma (LUSC) with a sample size larger than 500 were selected to construct nomogram models to confirm the prognostic value of EXOC3L1 in cancers. Additionally, the associations of EXOC3L1 with immune cell infiltrations were performed as well. Mechanistically, functional enrichment analysis was performed to explore potential signaling pathways that EXOC3L1 may involve in. Our study found that EXOC3L1 was differentially expressed in a variety of tumors and was associated with the clinical outcomes and immune microenvironment of several tumors, it may affect the occurrence and development of tumors through NOTCH signaling pathway, PI3K-AKT signaling pathway and immune-related pathways. In conclusion, we propose that EXOC3L1 may serve as a potential prognostic biomarker and a promising target for cancer immunotherapy in a variety of cancers.